Interrogating the tribal: the aporia of 'tribalism' in the sociological study of the Middle East. (20th March 2019) - Mohammadpour, Ahmad; Soleimani, Kamal
Abstract: In this paper, we intend to deconstruct the term 'tribalism' as a colonial category, which figures as a prominent concept in social studies on Kurds as well as the Middle East at large. Blithely used, tribalism has occupied a central place, especially in the existing scholarship on Kurdistan. Some earlier anthropological works have gone so far as to regard tribalism as the 'DNA' of Middle Eastern people. Drawing on recent studies on Latin America, Africa and Central Asia, we argue that the use of tribalism as if it is the natural constitution of Kurdish society has caused a significant misrepresentation and oversimplification of socio‐political life in Kurdistan as well as the broader Middle East. In a way, the existing body of scholarship on this region has reproduced statist‐nationalist discourses at the expense of dominated communities (e.g., Kurds). The historical context of both colonial powers and nation‐states 'combating tribes and tribalism' coincided with the emergence of the discourse of racial biopolitics. Thus, the use of the term tribalism to define certain nations or ethnic groups should not be viewed as merely an application of socio‐anthropological categories. Hence, we argue that the ethical aspects and implications of the use of tribalism by both colonial powers and later by nation‐states to define certain ethnic groups must not be overlooked.